Role of Topoisomerase IIβ in DNA Damage Response following IR and Etoposide - Nicola J. Sunter; Ian G. Cowell; Elaine Willmore; Gary P. Watters; Caroline A. Austin (Journal of Nucleic Acids)
The role of topoisomerase IIβ was investigated in cell lines exposed to two DNA damaging agents, ionising radiation (IR) or etoposide, a drug which acts on topoisomerase II. The appearance and resolution of γH2AX foci in murine embryonic fibroblast cell lines, wild type and null for DNA topoisomerase IIβ, was measured after exposure to ionising radiation (IR) or etoposide. Topoisomerase II-DNA adduct levels were also measured. IR rapidly triggered phosphorylation of histone H2AX, less phosphorylation was seen in TOP2β-/- cells, but the difference was not statistically significant. IR did not produce topoisomerase II-DNA adducts above control levels. Etoposide triggered the formation of topoisomerase II-DNA adducts and the phosphorylation of histone H2AX, the γH2AX foci appeared more slowly with etoposide than with IR. Topoisomerase II-DNA complexes in WT cells but not TOP2β-/- cells increased significantly at 24 hours with the proteasome inhibitor MG132, suggesting topoisomerase IIβ adducts are removed by the proteasome.